Dietary Corn Bran Fermented by Bacillus subtilis MA139 Decreased Gut Cellulolytic Bacteria and Microbiota Diversity in Finishing Pigs - Liu, Ping; Zhao, Jinbiao; Guo, Pingting; Lu, Wenqing; Geng, Zhengying; Levesque, Crystal L.; Johnston, Lee J.; Wang, Chunlin; Liu, Ling; Zhang, Jie; Ma, Ning; Qiao, Shiyan; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Solid-state fermentation feed by Bacillus subtilis MA139 can reduce insoluble dietary fiber content in vitro and improve growth performance in pigs. This study was aimed to investigate the effects of dietary corn bran (CB) fermented by B. subtilis on growth performance and gut microbiota composition in finishing pigs. A total of 60 finishing pigs were allocated into 3 dietary treatments, and pigs in each group received control (CON) diet, 10% CB diet, and 10% fermented CB (FCB) diet, respectively. The treatment lasted 21 d. Growth performance and nutrient digestibility were evaluated. Fecal samples were determined for bacterial community diversity by 16s rRNA gene amplicon sequencing. The dietary CB and FCB did not affect growth performance of finishing pigs. The digestibility of organic matter was decreased in both CB and FCB treatments compared with CON group (P < 0.05). The α-diversity for bacterial community analysis of Chao 1 in FCB treatment was lower than CON treatment (P < 0.05). The Fibrobacteres belongs to cellulolytic bacteria was isolated, and their relative abundance in CB group showed no difference between CON and FCB treatments. The abundance of Lachnospiraceae_NK4A136_group in CB treatment was higher than CON and FCB groups (P < 0.05), whereas the population of norank_f_Prevotellaceae was higher in FCB group compared to CON and CB groups (P < 0.05). In conclusion, dietary FCB decreased the abundance of bacterial communities, particularly the population of bacteria related to cellulolytic degradation.